Model of Religious Character Development Though Religious Activities at SMP Negeri 3 Surakarta - Nisa, Fatimah Khoirun; Azani, Muhammad Zakki (Universitas Muhammadiyah Surakarta, 2026)
The development of religious character is an important aspect of national education, as it aims to instill faith, moral values, and discipline in students. Schools play a strategic role in shaping students’ religious character through planned and continuous religious activities. This study aims to describe the model of religious character development through religious activities at SMP Negeri 3 Surakarta and to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving the principal, Islamic Education teachers, and students. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that religious character development is implemented through habituation of religious activities such as congregational prayers, dhuha prayers, Qur’an recitation, daily prayers, regular religious studies, celebration of religious holidays, and religious extracurricular activities. The success of this program is supported by teachers’ role modeling, student motivation, adequate facilities, and a supportive school environment. However, challenges remain, including low motivation among some students, limited parental support, and negative social environmental influences. Overall, the religious character development model at SMP Negeri 3 Surakarta has been implemented effectively and contributes positively to shaping students’ religious attitudes. Furthermore, this study provides practical implications for educational institution managers in designing religious character development strategies that are more adaptive and contextual to modern developments. The integration of routine religious activities with more innovative approaches is expected to increase active student engagement. This research also emphasizes the importance of sustainable collaboration between schools, parents, and the community in supporting the success of religious character building. Consequently, the model implemented is not merely ceremonial, but is also capable of fostering deep-rooted religious habits and awareness among students in their daily lives.